Keluarga Bersahabat Dengan Remaja (Keluarga Sahaja): Meningkatkan Keterampilan Keluarga Dalam Menyiapkan Reproduksi Sehat - Askrening; Khair Anwar, khalidatul; Yustiari; Asi, Melania (Poltekkes Kemenkes Kendari, 2024)
The impact of globalization and the advancement of information technology development has an impact on rapid social changes. The social changes in question include an increase in premarital sex behavior, extramarital pregnancy carried out by adolescents, as a result of changes in the values of family and community life. Reproductive health education is a very important strategy to prevent adolescents from falling into promiscuous sexual behaviors that endanger their reproductive health. Parents as the closest parties must have the knowledge and skills to provide reproductive health education to adolescents. However, there are still many parents in Bajoe village who still have low knowledge and skills in providing reproductive health education to their adolescents. This Community Service Program aims to build a